Towards Hispanic American cultural independence. Conceptual genesis of the "Letter from Jamaica" - Gómez García, Juan Guillermo (Estudios de Filosofía, 2008)
Among the documents of the former Peruvian Jesuit Juan Pablo Viscardo y Guzmán that the Venezuelan Francisco Miranda received from the North American plenipotentiary in England, Rufus King, was the "Letter addressed to the Spanish Americans." This documentary piece, considered "the first proclamation of Spanish American independence", had been originally written in French around 1792 as a testimony of protest of the situation of humiliation and submission that Spain had to its American colonies, to be presented before the English authorities. The enthusiasm that the "Letter" of the deceased Jesuit aroused in the fearsome and indefatigable conspirator Miranda, was unequivocal, to the point that he not only set out to translate and publish it (London, 1801), but also presented it, in his frustrated expedition to August 1806, as standard bearer of the liberating crusade. [Fragment]